2014
DOI: 10.1007/s00266-014-0308-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant Capsule Flaps and Grafts: A Review of the Literature

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors http://www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Consequently, we inserted this implant in both breasts through a new inframammary incision. The thinned out skin area on the left breast was supported with a triangle-shaped capsular-fascial flap of 6 cm in length, raised from the pectoral muscle [4,5]. An alternative solution would have been subpectoral implantation, which will support the recovery of thinned out skin in the upper but not in lower quadrants.…”
mentioning
confidence: 99%
“…Consequently, we inserted this implant in both breasts through a new inframammary incision. The thinned out skin area on the left breast was supported with a triangle-shaped capsular-fascial flap of 6 cm in length, raised from the pectoral muscle [4,5]. An alternative solution would have been subpectoral implantation, which will support the recovery of thinned out skin in the upper but not in lower quadrants.…”
mentioning
confidence: 99%
“…In our Institution, the ration of local complications after immediate breast reconstruction with implant comes to 11.6% of the cases. Traditional therapeutic approaches involve antibiotics, drainage, rinsing, capsulotomy, change of the device and primary closing of the wound after excision of the necrotic tissue (Weber & Hentz, 1986;Planas et al, 1995;Persichetti et al, 2014). However, they may also fail in cases of decreased tissue viability and irradiation.…”
Section: Successful Therapy Of Trapdoor Effectmentioning
confidence: 99%
“…Accompanying infection may contribute to this process. Although exposed implants are traditionally treated by insertion of a new one, many authors have reported successful salvage of implant (Forman et al, 1998;Ariyan, 2006;Behranwala et al, 2006) or alternative therapeutic strategies (Weber & Hentz, 1986;Planas et al, 1995;Abramo et al, 1999;Spear et al, 2004;Persichetti et al, 2014). However, these interventions may fail in case of previous radiotherapy or where tissue is injured or thin, necessitating implant removal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations